Analisis Studi Kelayakan Bisnis UMKM Gerobak Chicken Steak Dalam Mengekspansi Usaha di Kecamatan Medan Perjuangan - Sahara, Siti; Nasution, Salman (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This thesis discusses "Chicken Steak Cart". The main problem is whether the Chicken Steak Cart business is feasible or not for expansion. Business feasibility studies provide benefits for measuring and knowing whether or not a business is feasible or not. Business feasibility studies really help MSME players so that the business they run is successful or profitable. From several draft strategies taken, it is so that there can be an increase in MSME businesses that are more optimal. Decisions taken include that MSMEs need to expand into creative activities and have high economic added value by utilizing government support both in terms of funding, business training opportunities, strengthening institutions and more profitable business regulations. The purpose of this study is to determine the feasibility of the Chicken Steak Cart Business to be expanded even more broadly. By using this type of field research and qualitative approach.research carried out by being directly at the object, especially in an effort to collect data and various information carried out intensively, in detail and in depth on certain objects that require a comprehensive and thorough analysis.